Inclusive Learning Module in Merdeka Curriculum to Improve Language Skills of Children with Special Needs - Yuliana, Yuliana; Saman, Abdul; Herlina, Herlina; Kurnia, Rika; Bachtiar, Muhammad Yusri (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2025)
This study aimed to develop and assess an inclusive learning module designed to enhance the language development of children with special educational needs (CSEN) in an early childhood education setting. The module, grounded in Kurikulum Merdeka principles, was specifically tailored to address the language acquisition challenges faced by children with special needs. A Research and Development (R&D) approach, following the 4D model, was employed for module development, involving expert validation, teacher and parent feedback, and pilot testing. The results indicated significant improvements in vocabulary and sentence construction among all children involved in the study. Teachers and parents reported high satisfaction with the module’s usability and its effectiveness in supporting language development, confirming the importance of personalized educational resources. The study demonstrates the value of a structured, child-centered approach in fostering language skills in CSEN, particularly in inclusive early childhood education settings. The findings suggest that this module could serve as a model for other schools, but future research with a larger sample size and longer implementation period is needed to explore the long-term impact and applicability of such educational tools.